Oldest new genus of Myrmeleontidae (Neuroptera) from the Eocene Green River Formation - Makarkin, Vladimir N. (Zootaxa, 2017)
Epignopholeon sophiae gen. et sp. nov. (Neuroptera: Myrmeleontidae) is described from the early Eocene of the Green River Formation (Colorado, U.S.A.). It represents the oldest confident record of the family. The new genus is remarkable in that tergite 7 of the female is much shorter than its long sternite 7. The preserved wing venation shows that the genus belongs to the subfamily Myrmeleontinae, and most probably to the tribe Gnopholeontini. The discovery of this species is consistent with estimations of relatively dry and warm conditions during deposition of the upper Parachute Creek Member of the Green River Formation.